Potensi Blue Economy Pada Sektor Perikanan Dalam Meningkatkan Pendapatan UMKM : Studi Kasus Tambak Mulia Samudra Sidoarjo - Reginata Saharany Kustanti; Josephine Elliska Dinata; Anisa Lailatul Nikmah; Maria Yovita R.Pandin (Akuntansi, 2024)
The potential of marine resources in the fisheries sector has become a general illustration in developing the blue economy to encourage economic growth in Indonesia. The aim of the research is to determine the potential for a blue economy through fisheries sector businesses in fish farms that cultivate seaweed and milkfish. This research was carried out in Tambak Mulia Samudra, Sidoarjo Regency, East Java. This research uses primary and secondary data which is analyzed using a descriptive-qualitative approach. The research results show that there is waste processing and two environmentally friendly pond cultivation management systems in the marine ecosystem. The implementation of seaweed cultivation has also regulated the water area based on the carrying capacity of the water, so that it can produce optimal seaweed production, display cultivation components by protecting the water area and increasing economic welfare by opening employment opportunities for coastal communities.